Prevalence of Anaemia amongst non-pregnant women in Sirte at Ibn-Sina hospital over a period of ten years (2010-2020) - Alsanosi, Ibtisam (Sirte Journal of Medical Sciences, 2025)
Background: The World Health Organization (WHO) has reported that in 2019, 30% (539 million) of non-pregnant women were affected by anemia, with the highest prevalence in sub-Saharan Africa and Asia. Anaemia remains a major public health concern in developing countries, as it can affect individuals at any stage of life. The symptoms of anaemia are non-specific and can lead to reduced physical work capacity and productivity. The aim of the study is to estimate the prevalence of anaemia in non-pregnant women residing in Sirte City. Methods: This is a retrospective observational study that took place at Iben Sina Teaching Hospital in Sirte, Libya. The study included all case records of women above the age of 15 years who were admitted to the female medical ward at the hospital in the period between 2010 and 2020. The data was examined using Microsoft Excel 2019 and presented in tables and graphs. Results: The case records of 773 cases were reviewed and analyzed. The results revealed an estimated anemia (Hb <12g/dl) prevalence of 14.7% (114/773), the mean age of patients was 55 years and the mean Hb was 6.5 g/dl. Conclusion: The study showed that anaemia is prevalent in the admitted female population in the city of Sirte and a notable increase was noted in the last year of the study that could reflect capturing the real prevalence; this must be confirmed in subsequent studies that would also help in identifying risk factors and causes in this female population